Analisis Yuridis Kekuatan Hukum Jual Beli Tanah Dibawah Tangan (Overhands) dalam Proses Peralihan Hak Milik Atas Tanah: Studi Kasus Tanah Eks-Transmigrasi - Andi Asnizar Aziri Eka Putra; Triyana Syafitri; Herdiansyah Herdiansyah (MAN 4 Kota Pekanbaru, 2026)
Legal certainty over land is a fundamental principle of Indonesia’s agrarian legal system. Nevertheless, many land transfers, particularly involving ex-transmigration land, continue to be conducted through informal (under-hand) sale-and-purchase agreements, creating legal uncertainty and increasing the risk of disputes. This normative legal study employs a library research approach by analyzing legislation, legal literature, and court decisions. The findings show that informal land sale agreements are valid under Article 1320 of the Indonesian Civil Code, provided the legal requirements of a contract are fulfilled, thereby establishing binding obligations between the parties. However, such agreements do not constitute a legally effective transfer of ownership rights because they fail to satisfy the formal requirements of a PPAT deed and land registration as required under the Basic Agrarian Law and Government Regulation No. 24 of 1997, as amended by Government Regulation No. 18 of 2021. The study concludes that stronger institutional support, accelerated land registration, and greater legal awareness are essential to enhance legal certainty and prevent future land disputes involving ex-transmigration land.